Uses of Medicinal Plants Against Common Skin Problems in the Pokhara Valley - Dwa, Om Prasad (Janapriya Journal of Interdisciplinary Studies, 2023)
The present paper explores the different applications of medicinal plants to cure different skin diseases like boils, cuts, dandruff, eczema, herpes, inflammation, itching, leprosy, pimples, scabies, sores, syphilis, and wounds in rural wards in Pokhara Valley. Based on scientific studies and traditional knowledge, the present work identifies several potential medicinal plants, such as Achyranthus aspera, Ageratum conyzoides, Aloe vera, Amaranthus spinosus, Artemisia indica, Berberis aristate, Calotropis gigantea, Cassia tora, Curcuma longa, Oxalis corniculate, etc. The result of this execution is based on the user’s experience when they are suffering from such skin problems and the use of medicinal plants against those problems. The paper also discusses the advantages of utilizing medicinal plants with their minimum side effects, cost-effectiveness, and sustainable use.